Pengaruh Social Support Terhadap Pemberian ASI Eksklusif Wilayah Kerja Puskesmas Blangpidie - Cut Oktaviyana; Syarifah Masthura; Zia Novia Nelly (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Exclusive breastfeeding as early as possible can prevent infant death. Exclusive breastfeeding can prevent as many as 60% of the 10 million infant deaths that occur in developing countries every year, according to the World Health Organization (WHO). The percentage of exclusive breastfeeding coverage in Southwest Aceh district is 68%, but one of the factors that can increase this percentage is social support from families and health workers. The aim of the research is to determine the influence of social support on exclusive breastfeeding in the Blangpidie Community Health Center working area. Observational analytical survey research method with a cross-sectional approach. The population in the study was 87 breastfeeding mothers using the total sampling technique. The research was conducted from March 12 to March 21, 2023. The results of the simple logistic regression test analysis showed that the results showed that mothers who received social support-emotional (26%), and social support-assessment (35%), were able to influence mothers to continue to provide exclusive breastfeeding. Support from families and health workers is important to increase the prevalence of exclusive breastfeeding.